Implementation of a Halal Production System: Integrating Islamic Values in the Modern Economy - Ardine Zana Sakhi (ICO EDUSHA, 2024)
This research examines the implementation of a halal production system as part of the integration of Islamic values ​​in the modern economy. As global demand for halal products increases, both in domestic and international markets, it is important to understand the basic principles and challenges faced in their implementation. The halal production system not only refers to fulfilling aspects of Islamic ritual and law, but also touches on the ethical dimensions of business, which include honesty, justice and social responsibility. In this context, implementing a halal system can provide significant economic benefits, while strengthening a business culture of integrity. This research uses a qualitative approach to explore the factors that influence the implementation of the halal system, as well as the obstacles faced by industry players. The results show that support from the government is very important, both in terms of policies that facilitate the halal industry and in terms of educating the public about the importance of products that meet halal standards. In addition, the involvement of various parties, including halal certification bodies, business actors and consumers, is a key factor in ensuring halal products meet the expected standards. Thus, the integration of halal production systems in the modern economy is not only financially profitable, but also contributes to more ethical and sustainable economic development.   Keywords : Halal Production System, Modern Economy, Industrial Challenges.